Mechanistic insights into PTS2-mediated peroxisomal protein import : the co-receptor PEX5L drastically increases the interaction strength between the cargo protein and the receptor PEX7 - Kunze, Markus (2018)
The destination of peroxisomal matrix proteins is encoded by short peptide sequences, which have been characterized as peroxisomal targeting signals (PTS) residing either at the C terminus (PTS1) or close to the N terminus (PTS2). PTS2-carrying proteins interact with their cognate receptor protein PEX7 that mediates their transport to peroxisomes by a concerted action with a co-receptor protein, which in mammals is the PTS1 receptor PEX5L. Using a modified version of the mammalian two-hybrid assay, we demonstrate that the interaction strength between cargo and PEX7 is drastically increased in the presence of the co-receptor PEX5L. In addition, cargo binding is a prerequisite for the interaction between PEX7 and PEX5L and ectopic overexpression of PTS2-carrying cargo protein drastically increases the formation of PEX7-PEX5L complexes in this assay. Consistently, we find that the peroxisomal transfer of PEX7 depends on cargo binding and that ectopic overexpression of cargo protein stimulates this process. Thus, the sequential formation of a highly stable trimeric complex involving cargo protein, PEX7 and PEX5L stabilizes cargo binding and is a prerequisite for PTS2-mediated peroxisomal import.